Air Pollution and Sick-leaves - is there a Connection? A Case Study using Air Pollution Data from Oslo - Anett C. Hansen; Harald K. Selte (Statistics Norway, Research Department, 1997)
In recent years a growing number of studies have been discussing the relationship between air pollution and human health. The evidence in the literature for adverse health effects of several pol-lutants seems convincing. In our article we are concerned with to which extent these health effects in turn induce sick-leaves or other kinds of reduced labour productivity, which is important for as-sessment of air pollution costs. We analyse the association between sick-leaves in a large office in Oslo and the concentration of different air pollutants and find a significant relationship between the concentration of particulate matter and sick-leaves, while the associations with SO2 and NO2 are more ambiguous.
Keywords: C25; J21; Q25; 330; Air pollution; sick-leaves; logit specification